THE IMPLEMENTATION HUMAN RIGHTS IN INDONESIA - Nana Gerana; Safrudin (International Journal of Law and Legal Ethics, 2020)
Human rights are the most basic rights possessed by humans and this right is considered a gift given from God Almighty. Human rights are also protected by the State because the state also highly respects the human rights of a person by providing strict and binding rules for its citizens so that they do not perceive the human rights possessed by others. Capital punishment is one of the means to protect public interests of a social nature which are endangered by irreparable crimes. This paper is intended to analyze the capital punishment or death penalty in Indonesia in the context of human rights. The research method used in this paper is using the normative method. The results of this study indicated that the execution of the death penalty can be carried out for perpetrators of criminal acts who have crossed the human limit, endanger, and threaten many people.